Effects of Baduanjin exercise on the physical function of middle-aged and elderly people: a systematic review and meta-analysis of randomized controlled trials - Huiying Lin; Mingyue Wan; Yu Ye; Guohua Zheng (BMC, 2023)
Abstract Background and purpose Chinese mind-body exercise-Baduanjin has received increasing attention for health promotion among middle-aged and older adults in China, but there is a lack of high-quality evidence on its effectiveness. This systematic review and meta-analysis was conducted to investigate the effects of Baduanjin on physical function in middle-aged and older adults. Methods Seven electronic databases were searched for articles published before 22 June 2021 with the keywords Baduanjin exercise combined with physical-function-related outcomes. Risk of bias was assessed in the included studies, and data were analyzed using Review Manager software V5.3. Results Fifteen articles, including 14 randomized controlled trials, were included in this study. The results of the meta-analysis showed that Baduanjin significantly improved muscle strength (grip strength: SMD = 0.63, 95% CI 0.22 to 1.04, p = 0.003), balance ability (timed up-and-go test score: MD = -2.21, 95% CI -3.91 to -0.51, p = 0.01; one-leg stand test score: MD = 3.75, 95% CI 1.96 to 5.55, p < 0.0001; Berg balance scale score: MD = 4.16, 95% CI 2.49 to 5.83, p < 0.00001; strengthening Romberg's test result: SMD = 1.02, 95% CI 0.17 to 1.86, p = 0.02); and cardiorespiratory fitness (diastolic blood pressure: MD = -3.62, 95% CI -3.95 to -3.30, p < 0.00001; resting heart rate: MD = -1.30, 95% CI -1.57 to -1.03, p < 0.00001; step test: MD = 4.25, 95% CI 0.76 to 7.74, p = 0.02). No adverse events were reported. Conclusions Baduanjin exercise may be an effective intervention to improve physical function in the middle-aged and elderly population. However, more RCTs with larger sample sizes and more rigorous research designs are needed in the future to confirm the results.